The prediction Model of OCD personality based on complex trauma and object relation with mediating role of ego strength in conflicting couples - Bayani, Bita; Jafari, Asghar; Shafie Abadi, Abdollah; Hoseinian, Simin (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study aimed to study the predicting model of borderline personality based on complex trauma and object relation with mediating role of ego strength in conflicting couples. Methods: Method was descriptive-correlational. Population was all refereeing couples to counseling and psychological clinics in 2021 in Tehran. Using multi cluster sampling and cutting point >75 in MCMI-3, 205 participants with borderline and inclusion criteria were selected and completed the questionnaires of Markstorm and et al, s (1997) PIES, Milon-3, s (1997) MCMI-3, Bell's (1995) BORI, Borneshtian & et al, s (2003) CTQ. Data were analyzed by Pearson correlation and SEM. Findings: There is a positive and significant relationship between trauma and borderline and there is a negative and significant relationship between ego strength and borderline (p